Differences in chlorine and peracetic acid disinfection kinetics of Enterococcus faecalis and Escherichia fergusonii and their susceptible strains based on gene expressions and genomics. (15th September 2021) - Sahulka, Sierra Quinn; Bhattarai, Bishav; Bhattacharjee, Ananda S.; Tanner, Windy; Mahar, Rasool Bux; Goel, Ramesh
Highlights: Disinfection of antibiotic resistants and their susceptible counterparts was studied. Meropenem-resistant strain showed less log inactivation compared to susceptible strain. The resistant E. faecalis strain showed similar inactivation compared to susceptible one. Meropenem-resistant E. fergusonii showed an increase in gene expression of bla NDM-1 gene to chlorine. The meropenem-resistant E. fergusonii showed less log inactivation with a marginal significance. Abstract: This study was conducted to investigate mechanisms of cross-resistance to chlorine and peracetic acid (PAA) disinfectants by antibiotic-resistant bacteria. Our study evaluated chlorine and PAA based disinfection kinetics of erythromycin-resistant Enterococcus faecalis, meropenem-resistant Escherichia fergusonii, and susceptible strains of these species. Using the integrated second-order disinfectant decay model and first-order Chick-Watson's Law, it was found that the meropenem-resistant Escherichia fergusonii strain showed significantly less log inactivation compared to the susceptible E. fergusonii strain in response to both chlorine and PAA disinfection (p-value = 0.059, 3.5 × 10 −6 ). On the other hand, the susceptible Enterococcus faecalis strain showed similar log inactivation compared to the erythromycin-resistant strain in response to either treatment (p-value = 0.075, 0.28). Meropenem-resistant E. fergusonii showed an increase in gene expression of New Delhi metallo-β-lactamase ( bla NDM-1 ) gene to chlorine, but there was no increase in expression to PAA. Whole genome sequencing (WGS) was then conducted to elucidate the differences in genes among both resistant and susceptible table E. fergusonii strains. The average nucleotide identity (ANI) analysis of the draft genomes (>97% similarity) suggests that meropenem-resistant E. fergusonii (S1) and meropenem-susceptible E. fergusonii (S2) are the same species but different strains. Both strains have the same genes for oxidative stress pathways, oxidative scavenger genes, and nearly 40 different antibiotic efflux pump genes. The chromosomal and plasmid draft genomes of meropenem-resistant and susceptible E. fergusonii strains each have 65 and 52 antibiotic resistance genes, respectively. Of these, the resistant E. fergusonii strain harbored the extended-spectrum beta-lactamases bla CTX-M-15 and bla TEM-1 genes located on the chromosome, and a bla TEM-1 gene on the plasmid. The overall findings of this study are significant, as they reveal that antibiotic-resistant and susceptible strains of E. fergusonii exhibit different responses towards chlorine and PAA disinfection. Graphical abstract: Image, graphical abstract